2020
DOI: 10.33024/jkm.v6i3.1764
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Air Kelapa Hijau Dapat Menurunkan Dismenore

Abstract: Backgrund : Dysmenorrhea is the occurrence of discomfort during menstruation, usually with pain and centering on the lower abdomen. In Indonesia, in 2014 the incidence of dysmenorrhea was 64.25%, consisting of 54.89% of primary dysmenorrhea and 9.36% of secondary dysmenorrhea. One of the non-pharmacological treatments that can be done to treat pain in dysmenorrhea is to use green coconut water Purpose : It is known that there is an effect of giving green coconut water to decrease dysmenorrhea in Midwifery Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
2
0
4
Order By: Relevance
“…The results of this study are in line with research that has been carried out by (Rismaya, 2020) that in respondents who have been treated, it was found that there is a decrease in menstrual pain after being given green coconut water, this is because during menstruation the body excretes fluid and blood (Rismaya & Rosmiyati, 2020).…”
Section: The Effect Of Green Coconut Water On Reducing Dysmenorrhea Painsupporting
confidence: 89%
“…The results of this study are in line with research that has been carried out by (Rismaya, 2020) that in respondents who have been treated, it was found that there is a decrease in menstrual pain after being given green coconut water, this is because during menstruation the body excretes fluid and blood (Rismaya & Rosmiyati, 2020).…”
Section: The Effect Of Green Coconut Water On Reducing Dysmenorrhea Painsupporting
confidence: 89%
“…Sedangkan cara nonfarmakologis dapat dilakukan dengan kompres air hangat, kompres air dingin (Maimunah et al, 2017), hipnoterapi (Aprilyadi et al, 2018), terapi zink (Damayanti et al, 2020), endorphin massage (Septiani et al, 2021) dan lain sebagainya. Terapi disminorea secara non farmakologi juga dilakukan dengan mengkonsumsi beberapa jenis herbal seperti jahe merah (Mariza & Sunarsih, 2019), air kelapa hijau, (Rismaya et al, 2020), kunyit asam (Baiti et al, 2019), kombinasi jahe dengan dark chocholate (Faizah & Mukhoirotin, 2020) dan air rebusan wortel (Vidayati & Munawaroh, 2019). Dalam penelitian ini penulis mengkombinasikan antara wortel dengan dark chocolate dalam mengurangi intensitas disminorea pada remaja putri.…”
Section: Pendahuluanunclassified
“…Kandungan pada air kelapa hijau yaitu kalsium dan magnesium yang berguna untuk menurunkan ketegangan otot sertavitamin C untuk menghambat enzim cycloogsigenase (17). Penelitian oleh Khodijah dan Herfanda menunjukkan bahwa terdapat perbedaan hasil rata-rata dari dismenore yang dirasakan oleh responden, dimana sebelum diberikan air kelapa hijau yaitu 5,5 dan sesudah treatment turun menjadi 4,3 (18).…”
Section: Pendahuluanunclassified
“…Terdapat faktor yang memiliki pengaruh terhadap menurunnya tingkat dismenore pada responden, contohnya dengan mengatur pola makan yang baik dan melakukan istirahat tidur yang cukup. Dengan mengatur pola makan yang baik (asupan makanan seimbang) dan melakukan istirahat tidur yang cukup dapat meringankan nyeri perut ketika menstruasi (dismenore) tanpa mengkonsumsi obatobatan farmakologi ataupun obat tradisional (17).…”
Section: Gambaran Tingkat Dismenore Padaunclassified
See 1 more Smart Citation